Vos: Young, Poor and Vulgar in Eastern Bolivia? A Corpus Study on Voseo in WhatsApp Exchanges - Castedo, Tatiana Maranhão de; Marques Lucena, Rubens; Gomes da Silva, Carolina (Íkala, Revista de Lenguaje y Cultura, 2022)
This work aims to study the use of ‘vos’ in the Bolivian East, more specifically, in Santa Cruz de la Sierra. Based on a corpus composed of audio recordings of Whatsapp text messages between parents and children, our objective is to verify if the form of treatment used is compatible with the required situational variation. For the analysis, we used the theoretical assumptions of variationist sociolinguistics, intonational phonology and courtesy rules. The results show that the pronoun ‘vos’ has common and current usage in the Bolivian East to express not only familiarity, but also affection and trust. In addition, the intonation of the statements also helped to identify a courteous treatment.